Exploring the population interaction of Przewalski’s gazelle (Procapra przewalskii) based on the variations in gut microbiota across diverse geographic populations - Zhang, Jingjie; Song, Pengfei; Jiang, Feng; Zhang, Tongzuo (Frontiers in Microbiology, 2024)
The differences in gut microbiota among different populations, to a certain extent, reflect the degree of interaction between individuals within populations. To assess the interaction levels among several small populations of Przewalski's gazelle (Procapra przewalskii) (n = 105, from 7 different regions) based on differences in gut microbiota, we used the closely related Tibetan gazelle (P. picticaudata) (n = 52, from 7 different regions) as a control. We then compared the gut microbial communities between different populations of the two species using high-throughput sequencing of the 16S rRNA gene. The results showed that within a 100 km geographical distance, the intergroup differences in relative abundance of dominant bacteria, α-diversity, β-diversity, and functional metabolism abundance were higher or significantly higher in Przewalski's gazelle (narrowly distributed species) compared to the Tibetan gazelle (widely distributed species). Additionally, the proportion of shared OTUs between groups in Przewalski's gazelle was significantly lower than in Tibetan gazelle (P < 0.05). Additionally, neutral community model results also showed lower dispersal limitation in the Tibetan gazelle compared to Przewalski's gazelle. Therefore, based on the above results, we comprehensively speculate that the spatial interaction degree of Przewalski's gazelle in different habitat patches is relatively low. This study, starting from the perspective of gut microbiota, adopts a non-genetic perspective or method to assess whether there is, or to what extent there is, close interaction between species populations.